Difficulties in reading comprehension a case study of the first-year English major students at Tay Do University = - Châu, Thanh Hải (Can Tho University, 2009)
The reasearch aims what common difficulties may influence on reading comprehension, and suggestion of some appropriate solutions to overcome these difficulties.